The Utilization of Digital Tools in the Classroom: A Phenomenological Study of University Educators' Experiences (The Educator Journal, 2025)
With an emphasis on their personal experiences, this qualitative study investigates how college instructors incorporate digital resources into their lesson plans. The study explores the kinds of digital tools used, perceived advantages, difficulties, and methods for getting beyond obstacles to successful technology integration, all while adhering to a phenomenological research style. Three university-level instructors from Drabya Shah Multiple Campus in Gorkha, Nepal, participated in semi-structured interviews. The use of digital tools in the classroom, the advantages of digital integration, the difficulties faced by teachers, adaptive strategies, institutional support, and the necessity of policy and curriculum alignment were the six main themes that emerged from the data analysis using thematic analysis (Braun & Clarke, 2006). Results show that although digital tools improve accessibility, engagement, and the effectiveness of education, teachers still have to deal with severe infrastructure constraints, uneven internet connection, device inequalities, and a lack of proper training. Through individual endeavors, teamwork, and calculated adjustments, participants showed resilience in spite of these limitations. By emphasizing the need for systemic changes in institutional infrastructure, teacher preparation programs, and educational policies to guarantee sustainable technology integration, the study adds to the conversation on digital pedagogy. Teachers, organizations, and legislators are given suggestions on how to promote the equitable and purposeful use of digital tools in higher education environments.